2005
DOI: 10.1002/pen.20410
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of shrinkage and warpage behavior for microcellular and conventional injection molding

Abstract: This research investigated the effects of processing conditions on the shrinkage and warpage (S&W) behavior of a box‐shaped, polypropylene part using conventional and microcellular injection molding. Two sets of 26‐1 fractional factorial design of experiments (DOE) were employed to perform the experiments and proper statistical theory was used to analyze the data. After the injection molding process reached steady state, molded samples were collected and measured using an optical coordinate measuring machine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 15 publications
2
55
0
Order By: Relevance
“…It demonstrates that the trained SVR surrogate models, which require a reasonably small amount of computational resources, possess good predictive capability for substituting the complete simulations after they are properly trained. It is also found that the minimum S&W corresponding to the optimal process conditions determined by the SVR models is smaller than the minimal S&W predicted by the experimental regression [20]. This is because the surrogate models established here are more flexible in determining the optimal conditions; and these optima need not to be restricted to the fixed levels as used in conventional factorial DOE for actual molding experiments.…”
Section: Validation and Process Optimization For A Box Partmentioning
confidence: 79%
See 3 more Smart Citations
“…It demonstrates that the trained SVR surrogate models, which require a reasonably small amount of computational resources, possess good predictive capability for substituting the complete simulations after they are properly trained. It is also found that the minimum S&W corresponding to the optimal process conditions determined by the SVR models is smaller than the minimal S&W predicted by the experimental regression [20]. This is because the surrogate models established here are more flexible in determining the optimal conditions; and these optima need not to be restricted to the fixed levels as used in conventional factorial DOE for actual molding experiments.…”
Section: Validation and Process Optimization For A Box Partmentioning
confidence: 79%
“…Table 3 also lists the optimal process conditions obtained from experimental regression for minimizing the S&W, as reported in [20]. From the comparison, the difference between the results from the surrogate models and the simulation is quite small (5.57 %), which suggests that the trained surrogate models can reproduce the simulation results reasonably well.…”
Section: Validation and Process Optimization For A Box Partmentioning
confidence: 89%
See 2 more Smart Citations
“…Heat transfer perpendicular to the cavity wall can be retarded because the film is attached on one side of the cavity wall and two different polymers are used as the film and substrate. [5] Many studies have been carried out to investigate the effects of processing conditions on the warpage and residual stress distribution of injection molded parts without any inserted film; [6][7][8][9][10][11][12][13][14][15][16][17] however, investigations of the FIM process have rarely been reported. It is essential to understand the residual stress distribution and to predict the viscoelastic deformation of the molded part for the practical application of FIM to industrial end-user products.…”
Section: Introductionmentioning
confidence: 99%